Distinguished and Unique Fiction Writer Aziz Ahmed's Intellectual History: ممتاز و منفردفکشن نگار عزیز احمد کی فکری تاریخ نویسی (DARYAFT, 2023)
Aziz Ahmed is an outstanding fiction writer who holds a unique place in Urdu fiction for his style and contribution. His creative works are adored and appreciated by a wide circle of readers and critics. He pens down the cultural historiography of South Asian Muslims and his grip of writing about the political and social life of this region and Europe is examplary one and holds great significance. This article critically examines, evaluates and analyses his works of Urdu fiction both novels and short stories along with his works related with literary criticism.
Keywords: Fiction, Writer, Unique, Creative, Critics, Cultural, Histography, South Asian Muslims, Political.